Peran Kedudukan Akuntansi Keuangan Daerah Dalam Pengelolaan Keuangan Daerah Yang Efektif - Maharani Safitri; Sonny Fransisco Siboro; Amara Kasih Ariningrum; Muhammad Arul Andreandra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to thoroughly examine how accounting is viewed and applied in the regional financial framework. This type of research uses a literature study in the form of a qualitative approach. The results of this study indicate that the effective application of AKD in accordance with SAP is the key to realizing open, accountable, and sustainable regional financial management.